2018
DOI: 10.1097/bot.0000000000001186
|View full text |Cite
|
Sign up to set email alerts
|

Cost Determinants in the 90-Day Management of Isolated Ankle Fractures at a Large Urban Academic Hospital

Abstract: Isolated operative ankle fractures are a prime target for EOC cost containment strategy protocols. Our institutional cost analysis study suggests that independent financial clinical risk factors in this treatment cohort includes podiatry as the treating surgical service and patients with an American Society of Anesthesiologists score ≥3, with the former also independently increasing total postdischarge costs in the 90-day EOC. Outpatient procedures were associated with about a one-third reduction in total cost… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
17
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 22 publications
1
17
0
Order By: Relevance
“…2-year follow-up) and increased non-home discharges 18 Easterlin et al demonstrated similar findings in total knee arthroplasty (TKA) for patients recorded in the NSQIP database. Their results indicated that age was an independent risk factor for adverse outcomes following TKA after controlling for comorbid conditions.…”
Section: Discussionmentioning
confidence: 69%
See 2 more Smart Citations
“…2-year follow-up) and increased non-home discharges 18 Easterlin et al demonstrated similar findings in total knee arthroplasty (TKA) for patients recorded in the NSQIP database. Their results indicated that age was an independent risk factor for adverse outcomes following TKA after controlling for comorbid conditions.…”
Section: Discussionmentioning
confidence: 69%
“… 8 , 17 Kennedy et al described a “snowballing” of complications in some patients ≥80 years following THA, where multiple sequential adverse events can lead to rapid deterioration. Other studies of nonagenarian patients after hip fracture repair reported increased medical complications, greater risk of mortality (in-hospital through 2-year follow-up) and increased non-home discharges 18 Easterlin et al demonstrated similar findings in total knee arthroplasty (TKA) for patients recorded in the NSQIP database. Their results indicated that age was an independent risk factor for adverse outcomes following TKA after controlling for comorbid conditions.…”
Section: Discussionmentioning
confidence: 81%
See 1 more Smart Citation
“…16,17 Considering the differences in injury severity and complication rates, the benefits of fibula IMN fixation of malleolar ankle fractures may be even more pronounced in pilon fractures. 9,10,14,15 Intramedullary fibula fixation of pilon fractures has only been investigated in a few small series. Stewart et al 9 reported on distally locked fibular IMN in 23 pilon fractures and demonstrated a 100% union rate, no wound complications, no revision surgeries, and one symptomatic fibula implant removal.…”
Section: Discussionmentioning
confidence: 99%
“…However, when one study isolated cases to outpatient surgery and surgery-related complaints, this range narrowed to approximately 11-17%, with pain being amongst the most common reasons for ED presentation [19,20]. In terms of readmissions, two larger studies investigating readmissions after surgical fixation of an ankle fracture showed readmission rates varying from approximately 3-5%, with infections being reported as the most common cause in one study [21,22]. Interestingly, these results are similar with the elective orthopaedic surgery data.…”
Section: Discussionmentioning
confidence: 99%